2016
DOI: 10.1016/j.biortech.2016.02.125
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of phosphate from aqueous solution by magnesium oxide decorated magnetic biochar and its potential as phosphate-based fertilizer substitute

Abstract: The present study deals with the preparation of a novel MgO-impregnated magnetic biochar (MMSB) for phosphate recovery from aqueous solution. The MMSB was evaluated against sugarcane harvest residue biochar (SB) and magnetic biochar without Mg (MSB). The results showed that increasing Mg content in MMSB greatly improved the phosphate adsorption compared to SB and MSB, with 20% Mg-impregnated MMSB (20MMSB) recovering more than 99.5% phosphate from aqueous solution. Phosphate adsorption capacity of 20MMSB was 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
86
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 336 publications
(94 citation statements)
references
References 35 publications
7
86
1
Order By: Relevance
“…About 50 g of sycamore tree sawdust was immersed into the prepared FeCl 3 solution (1 L, 0.1 mol/L) for 24 h, and then, the separated solid mixture was oven‐dried overnight (80 °C). After that, both the FeCl 3 ‐treated and the pristine sawdust was pyrolyzed in a furnace at 550 °C in a N 2 atmosphere for 1 h, as reported before . The pyrolyzed products of the nontreated sawdust and treated sawdust were called BC and BC–Fe 3 O 4 (MBC), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 50 g of sycamore tree sawdust was immersed into the prepared FeCl 3 solution (1 L, 0.1 mol/L) for 24 h, and then, the separated solid mixture was oven‐dried overnight (80 °C). After that, both the FeCl 3 ‐treated and the pristine sawdust was pyrolyzed in a furnace at 550 °C in a N 2 atmosphere for 1 h, as reported before . The pyrolyzed products of the nontreated sawdust and treated sawdust were called BC and BC–Fe 3 O 4 (MBC), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, it is difficult for BC to be reused and separated after adsorption treatments because of its low density and fine dispersion of powder particles. Recently, some researchers developed engineered magnetic biochar (MBC) adsorbents to solve its deficiency . Although the adsorption capabilities of BC or synthesized MBC adsorbents were still very limited, improvements in these BC adsorbents' capacities were still needed to make them more practicable .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more, protein decomposition could give rise to an increase in C/N. 33,34 From the surface characteristics of biochar, it could be concluded that high temperatures had a positive inuence on improving the BET surface area. Compared with the heavy metal content in sludge, the contents in biochar became higher.…”
mentioning
confidence: 99%
“…However, the TP removal increased from 91.9 % to 96.3 % when the CaCl 2 /TP molar ratio was more than 1.6:1. The residual pH by MgCl 2 and CaCl 2 changed from 13 to 11.5 and 13 to 12 after the precipitation reaction, respectively, indicating MgCl 2 and CaCl 2 consumed less alkalinity than FeCl 3 in the precipitation reaction . Figure also shows that the TP removal rates obtained by FeCl 3 , AlCl 3 , MgCl 2 , and CaCl 2 were 84.2 %, 79.8 %, 78.6 %, and 96.3 % at the optimal Metal/TP molar ratio, respectively.…”
Section: Resultsmentioning
confidence: 85%